In-situ construction method and application of heterogeneous oxygen electrode of solid oxide battery
The in-situ construction of a heterogeneous oxygen electrode with NiFe2O4 nano-spinel catalysts addresses the polarization loss and stability issues by ensuring even distribution and nested structure, enhancing catalytic activity and efficiency in RSOCs.
Patent Information
- Application Number
- CN202411402261.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-31
AI Technical Summary
The large polarization loss and poor stability of the oxygen electrode in reversible solid oxide cells (RSOCs) limit their industrial application, particularly due to the lack of effective methods for achieving close contact and uniform distribution of nanocatalytic particles with the matrix.
An in-situ construction method for a heterogeneous oxygen electrode involving doping transition metal Ni into La x Sr 1-x Fe 0.9 Mo 0.1 O 3-δ powder, followed by mixing with an organic binder and a pore-forming agent, deposition on an electrolyte, high-temperature calcination, reduction, and oxidation to form NiFe2O4 nano-spinel catalysts, which are evenly distributed and nested with the substrate.
The method simplifies the preparation process, avoids nanoparticle sintering and agglomeration, and enhances catalytic activity for oxygen evolution and reduction reactions, improving the output performance and energy conversion efficiency of solid oxide fuel cells and electrolyzers.
Smart Images

Figure CN119230851A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid oxide fuel cells, solid oxide electrolytic cells and reversible solid oxide cells, and in particular relates to an in-situ construction method and application of a heterogeneous oxygen electrode of a solid oxide cell. Background Art
[0002] Nowadays, energy resource constraints and environmental risk challenges are the focus of world attention and have become two major issues affecting the sustainable development of human society in the 21st century. Developing a low-carbon economy with low energy consumption and low emissions, coordinating green and low-carbon development of energy and energy supply, and achieving sustainable development are becoming the common choice for economic development in countries around the world. Reversible solid oxide cells (RSOCs) are a clean and efficient electrochemical energy conversion device. When people have a high demand for electricity, RSOCs can work as solid oxide fuel cells (SOFCs) to convert the chemical energy in stored fuel gases such as H2, CO, and CH4 into electricity; when people have a low demand for electricity, or when the power system is oversupplied, RSOCs can work as electrolytic cells (SOECs) to use surplus electricity and industrial waste heat for high-temperature electrolysis of water or CO2 to prepare clean energy such as hydrogen for storage, that is, converting electricity into chemical energy. Therefore, RSOCs can realize the "fuel-electricity" cycle, alleviate and regulate the society's demand for energy, and play a role in shifting peaks and filling valleys. Among the three components of RSOCs, the oxygen electrode is an important reaction site for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Its large polarization loss and poor stability have become the main factors limiting the industrial application of RSOCs.
[0003] Fe-based perovskite oxides have the advantages of low cost and abundant content. 1-x Sr x FeO 3-δ The thermal expansion coefficient (TEC) of the oxide matches that of commonly used electrolytes, and it has high mixed ion-electron conductivity and oxygen surface exchange coefficient, as well as good catalytic activity and long-term stability. In addition, it has better redox stability in the oxidation of carbon-containing fuels and the electrolysis of carbon dioxide, and is more inert to coking. 1-x Sr x Fe 1-y Mo y O 3-δ It has become a hot topic in cobalt-free oxygen electrodes. 1-x Sr x Fe 1-y Mo y O 3-δ The research on oxygen electrodes mainly focuses on the composite with electrolyte materials, while the research on La1-x Sr x Fe 1-y Mo y O 3-δ There has been little research on the modification of oxygen electrodes with nanocatalysts and the modification of their microstructure.
[0004] Constructing nanocatalytic particles can improve the conductivity, electrocatalytic activity, and stability of electrode materials by generating a synergistic effect. Due to the excellent properties of the heterointerface, some scholars have prepared them by impregnation and mechanical mixing methods. However, the commonly used methods cannot well achieve the close contact and uniform distribution between the nanocatalytic particles and the matrix, seriously weakening the performance of the electrode. Summary of the Invention
[0005] The present invention overcomes the deficiencies of the prior art and provides an in-situ construction method for a heterogeneous oxygen electrode of a solid oxide battery in view of the problems of large polarization loss and poor stability of the oxygen electrode. An in-situ construction method for a heterogeneous oxygen electrode of a solid oxide battery is provided, which includes the following steps:
[0006] To solve the above technical problems, the technical solution adopted by the present invention is as follows: An in-situ construction method for a heterogeneous oxygen electrode of a solid oxide battery, including the following steps: In the first step, the transition metal element Ni is doped into the B site of the ABO3-type perovskite La x Sr 1-x Fe 0.9 Mo 0.1 O 3-δ oxide to prepare La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ powder, where 0.5 ≤ x < 1 and 0 < y < 0.2; or the transition metal element Ni is doped into the A-site-deficient ABO3-type perovskite La x Sr 1-x Fe 0.9 Mo 0.1 O 3-δ oxide to obtain a defective (La x Sr1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder, where 0.5≤x<1, 0 <y<0.2; The second step is to x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe 0.9- y Ni y Mo 0.1 O 3-δ The powder is mixed with an organic binder and a pore-forming agent and ground into an electrode slurry, and the slurry is uniformly deposited, cast or coated on the surface of the electrolyte, and calcined at a high temperature to form a porous electrode; the calcination temperature is 900°C-1100°C, and the calcination time is 2-10 hours; The third step is to reduce the electrode in a high temperature H2 atmosphere to achieve in-situ precipitation of Fe-Ni nano-alloy particles on the surface of the perovskite matrix. The high temperature reduction temperature is 800 ℃-900 ℃ and the H2 flow rate is 10-80 mL·min -1 , annealing time is 5-20 hours; The fourth step is to oxidize the electrode obtained in the third step at high temperature in the air to convert the Fe-Ni nano-alloy particles into NiFe2O4 nano-spinel catalysts, thereby obtaining an electrode modified with NiFe2O4 nano-spinel catalytic particles, i.e., a heterogeneous oxygen electrode for a solid oxide battery; the high-temperature oxidation temperature is 800°C-1000°C, and the annealing time is 5-20 hours.
[0007] As a further limitation of the technical solution of the present invention, the La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ The powder is synthesized by a sol-gel method, a glycine combustion method or a solid phase method.
[0008] As a further limitation of the technical solution of the present invention, the sol-gel synthesis method comprises the following steps: (1) Combine La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O and (NH4)6Mo7O 24 4H2O was dissolved in deionized water, and CA and EDTA were added as complexing agents; (2) The obtained mixed solution was continuously stirred in a water bath at 80°C until a viscous brown jelly was obtained; (3) Drying the obtained colloid in a drying oven at 200°C for 12 hours to completely dry the colloid to obtain a fluffy black xerogel; (4) Grind the obtained dry gel in a mortar until it is completely mixed; (5) Calcine the ground product at 900°C-1100°C for 5-20 hours to obtain La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ or defective type (La 0.5 Sr 0.5 ) 0.95 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ powder.
[0009] As a further limitation of the technical solution of the present invention, in step (1) of the sol-gel synthesis method, the molar ratio of total metal ions, CA and EDTA is 1:1.5:1.
[0010] As a further limitation of the technical solution of the present invention, the electrolyte is LaGaO3 doped with Mg and Sr, gadolinium oxide doped cerium oxide, samarium oxide doped cerium oxide oxygen ion conductive electrolyte, or yttria-stabilized zirconia electrolyte with the above electrolyte added to the surface as an isolation layer, or BaCeO3-based, SrCeO3-based, SrZrO3-based and BaZrO3-based ion conductive electrolyte.
[0011] As a further limitation of the technical solution of the present invention, the La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe0.9-y Ni y Mo 0.1 O 3-δ The mass ratio of powder to organic binder and pore-forming agent is 5:5:1.
[0012] As a further limitation of the technical solution of the present invention, a certain proportion of electrolyte powder is also mixed into the electrode slurry.
[0013] As a further limitation of the technical solution of the present invention, in the first step, the transition metal element Ni doped at the B position is replaced by at least one of Co and Cu, or replaced by any of Ni, Co and Cu.
[0014] The present invention also provides a solid oxide battery heterogeneous oxygen electrode prepared by the above-mentioned in-situ construction method.
[0015] In addition, the present invention also provides the use of the above-mentioned solid oxide battery heterogeneous oxygen electrode in the cathode of a solid oxide fuel cell, the anode of a solid oxide electrolysis cell or the oxygen electrode of a reversible solid oxide fuel cell.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. Compared with the preparation of nanocatalytic particle-modified electrodes by solution impregnation and mechanical mixing, the present invention avoids repeated impregnation and calcination processes, simplifies the preparation process, saves preparation time, and the in-situ constructed nanoparticles form a nested structure with the substrate, and the precipitated particles are more evenly distributed, avoiding the problem of nanoparticle sintering and agglomeration existing in the solution impregnation and mechanical mixing methods.
[0017] 2. With La 0.5 Sr 0.5 Fe 0.9 Mo 0.1 O 3-δ Compared with solid oxide materials, the nanocatalytic particle materials in situ constructed by element doping and reduction-reoxidation technology have higher catalytic activity in oxygen evolution and oxygen reduction reactions. Applying them to the cathode of solid oxide fuel cells, the anode of solid oxide electrolyzers and the oxygen electrode of reversible solid oxide fuel cells can further improve the output performance of the battery and improve the energy conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is La in Examples 1 and 2 of the present invention 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ and defective type (La 0.5 Sr 0.5 ) 0.95Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ XRD pattern of .
[0019] Figure 2 is La in Example 1 of the present invention 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ SEM image of .
[0020] Figure 3 This is the power density curve of a single cell in SOFC mode in Example 1 of the present invention.
[0021] Figure 4 This is the output performance curve of the single cell in Example 1 of the present invention under the SOEC mode.
[0022] Figure 5 The defect type (La 0.5 Sr 0.5 ) 0.95 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ SEM image of .
[0023] Figure 6 This is the power density curve of a single cell in SOFC mode in Example 2 of the present invention.
[0024] Figure 7 This is the power density curve of a single cell in SOEC mode in Example 2 of the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments. Example 1
[0026] La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ Preparation of oxygen electrode materials: According to the synthesis of 0.02 mol La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δStoichiometry of (LSFNM) 4.3301 g lanthanum nitrate, 2.1163 g strontium nitrate, 6.464 g iron nitrate, 0.5816 g nickel nitrate and 0.3531 g ammonium molybdate powder were weighed and dissolved in deionized water, and 12.6084 g citric acid (CA) and 11.6896 g ethylenediaminetetraacetic acid (EDTA) were added as complexing agents, where total metal ions: CA: EDTA = 1:1.5:1 (molar ratio); The resulting precursor solution was continuously stirred in a water bath at 80 °C to obtain a viscous brown jelly; The obtained colloid was dried in a drying oven at 200°C for 12 hours to completely dry the colloid to obtain a fluffy black xerogel; The resulting powder is thoroughly ground in a mortar until it is completely mixed; The ground product was calcined at 1100 °C for 10 h to obtain La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ powder; La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ The powder, organic binder (92% pineol and 8% ethyl cellulose) and pore former were mixed in a mass ratio of 5:5:1 and ground in an agate mortar for 3 h to obtain a well-mixed electrode slurry; La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ The slurry was coated on a YSZ electrolyte with GDC as an isolation layer as the working electrode (WE) and sintered at 1100 °C for 5 h; It was reduced at 800 °C for 10 h in pure H2 atmosphere to obtain Fe-Ni nanoalloy particle-modified LSFNM electrode (R-LSFNM); It was placed in air and oxidized at 800 °C for 10 h to obtain a LSFNM electrode modified with NiFe2O4 nano-spinel catalytic particles (sp-LSFNM); Silver paste (DAD-87, Shanghai Synthetic Resin Research Institute, China) was applied on the other side of the YSZ electrolyte support as the counter electrode (CE), which was symmetrical to the working electrode. The silver reference electrode (RE) was located on the same side of the oxygen electrode and kept a certain distance from the oxygen electrode to obtain an effective area of 0.26 cm 2 The half-cells were analyzed by scanning electron microscopy to understand the microscopic morphology and structure of various oxygen electrodes.
[0027] Ni-YSZ was selected as the hydrogen electrode of RSOCs, and a hydrogen electrode-supported Ni-YSZ / YSZ / GDC / sp-LSFNM single cell was prepared; The single cell was sealed in an alumina ceramic tube for electrochemical performance testing. Before the test, NiO was reduced to Ni in hydrogen at 650 °C. In SOFC mode, the flow rate was 50 mL min -1 Wet H2 (3% H2O) was delivered to the Ni-YSZ electrode, and the oxygen electrode was exposed to the air atmosphere. In the SOEC mode, a mixed gas of water vapor, H2, and Ar was delivered to the Ni-YSZ electrode, where the gas volume ratio of H2 to Ar was 75:25 and the total flow rate was 100 ml min -1 .
[0028] The sp-LSFNM oxygen electrode material obtained in Example 1 was characterized by XRD. Figure 1 As shown, LSFNM powder with in situ constructed NiFe2O4 nano-spinel catalytic particles was obtained.
[0029] The microscopic morphology of the half-cell obtained in Example 1 was analyzed. Figure 2 As shown in the figure, the LSFNM series oxygen electrodes all have a uniform porous structure, which is conducive to gas diffusion. After reduction treatment, a small amount of nanoparticles are precipitated on the surface of the R-LSFNM oxygen electrode. After oxidation treatment again, the nanoparticles on the surface of the sp-LSFNM oxygen electrode still exist, which is consistent with the results of XRD. The NiFe2O4 nanocatalyst precipitated on the surface of the sp-LSFNM oxygen electrode can expand the three-phase reaction interface, increase the reaction sites required for oxygen reduction and precipitation reactions, and significantly improve the electrocatalytic activity.
[0030] The electrochemical output performance of the single cell obtained in Example 1 in SOFC and SOEC modes was tested using a CHI660E electrochemical workstation (CH Instrument Co., Ltd., Shanghai, China) at 650°C-800°C. At 800°C, the maximum power density (MPD) of the LSFM, LSFNM and sp-LSFNM oxygen electrodes was 475, 539 and 741 mW·cm, respectively. -2 ( Figure 3), the electrolysis current densities at an electrolysis voltage of 1.5 V were 930, 1404, and 1827 mA·cm -2 ( Figure 4 ). Obviously, the in-situ precipitation of nanocatalysts improves the catalytic activity of the electrode. Example 2
[0031] Defective (La 0.5 Sr 0.5 ) 0.95 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ Preparation of oxygen electrode materials: 0.02 mol (La 0.5 Sr 0.5 ) 0.95 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ Synthesis and electrochemical performance testing of (LSFNM95).
[0032] According to the stoichiometric amount of synthesizing 0.02 mol LSFNM95, 4.1136 g lanthanum nitrate, 2.0105 g strontium nitrate, 6.464 g iron nitrate, 0.5816 g nickel nitrate and 0.3531 g ammonium molybdate powder were dissolved in deionized water, and 12.6084 g citric acid (CA) and 11.6896 g ethylenediaminetetraacetic acid (EDTA) were added as complexing agents, where the total metal ions: CA: EDTA = 1:1.5:1; According to steps 2)-5) of Example 1, LSFNM95 powder was obtained; 3) According to steps 6) to 9) of Example 1, a LSFNM95 electrode modified with NiFe2O4 nano-spinel catalytic particles (sp-LSFNM95) was prepared.
[0033] The sp-LSFNM95 material obtained in Example 2 was characterized by XRD. Figure 1 As shown, LSFNM95 powder with in situ constructed NiFe2O4 nano-spinel catalytic particles was obtained.
[0034] The microscopic morphology of the half-cell obtained in Example 2 was analyzed. Figure 5 As shown, after treatment of the defective LSFNM95 oxygen electrode, the number of nanocatalyst particles precipitated on the perovskite surface increased significantly and was evenly dispersed on the surface, which is conducive to maximizing the synergistic effect.
[0035] The electrochemical output performance of the single cell obtained in Example 2 in SOFC and SOEC modes was tested using a CHI660E electrochemical workstation (CH Instrument Co., Ltd., Shanghai, China) at 650°C-800°C. At 800°C, the maximum power density (MPD) of the LSFNM95 and sp-LSFNM95 oxygen electrodes was 651 and 879 mW·cm, respectively. -2 ( Figure 6 ), the electrolysis current densities at an electrolysis voltage of 1.5 V were 1552 and 2206 mA·cm -2 ( Figure 7 ), the in-situ precipitation of nanocatalysts significantly improved the catalytic activity of the electrode.
[0036] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any modifications within the present invention should be included in the protection scope of the present invention.
Claims
1. A method for in-situ construction of a heterogeneous oxygen electrode for a solid oxide battery, characterized in that: The steps include: First step, dope the transition metal element Ni into the B site of ABO3-type perovskite La x Sr 1-x Fe 0.9 Mo 0.1 O 3-δ oxide to obtain La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ powder, where 0.5 ≤ x < 1, 0 < y < 0.2; or dope the transition metal element Ni into the A-site-deficient ABO3-type perovskite La x Sr 1-x Fe 0.9 Mo 0.1 O 3-δ oxide to obtain defective (La x Sr 1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ powder, where 0.5 ≤ x < 1, 0 < y < 0.2; The second step is to x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ The powder is mixed with an organic binder and a pore-forming agent and ground into an electrode slurry, and the slurry is uniformly deposited, cast or coated on the surface of the electrolyte, and calcined at a high temperature to form a porous electrode; the calcination temperature is 900°C-1100°C, and the calcination time is 2-10 hours; The third step is to reduce the electrode in a high temperature H2 atmosphere to achieve in-situ precipitation of Fe-Ni nano-alloy particles on the surface of the perovskite matrix. The high temperature reduction temperature is 800 ℃-900 ℃ and the H2 flow rate is 10-80 mL·min -1 , annealing time is 5-20 hours; The fourth step is to oxidize the electrode obtained in the third step at high temperature in the air to convert the Fe-Ni nano-alloy particles into NiFe2O4 nano-spinel catalysts, thereby obtaining an electrode modified with NiFe2O4 nano-spinel catalytic particles, i.e., a heterogeneous oxygen electrode for a solid oxide battery; the high-temperature oxidation temperature is 800°C-1000°C, and the annealing time is 5-20 hours.
2. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 1, characterized in that: The La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ The powder is synthesized by a sol-gel method, a glycine combustion method or a solid phase method.
3. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 2, characterized in that: The sol-gel synthesis method comprises the following steps: (1) Combine La(NO3)3·6H2O, Sr(NO3)2, Fe(NO3)3·9H2O, Ni(NO3)2·6H2O and (NH4)6Mo7O 24 4H2O was dissolved in deionized water, and CA and EDTA were added as complexing agents; (2) The obtained mixed solution was continuously stirred in a water bath at 80°C until a viscous brown jelly was obtained; (3) Drying the obtained colloid in a drying oven at 200°C for 12 hours to completely dry the colloid to obtain a fluffy black xerogel; (4) Grind the obtained dry gel in a mortar until it is completely mixed; (5) Calcine the ground product at 900°C-1100°C for 5-20 hours to obtain La 0.5 Sr 0.5 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ or defective type (La 0.5 Sr 0.5 ) 0.95 Fe 0.8 Ni 0.1 Mo 0.1 O 3-δ powder.
4. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 3, characterized in that: The molar ratio of total metal ions, CA and EDTA in step (1) of the sol-gel synthesis method is 1:1.5:
1.
5. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 1, characterized in that: The electrolyte is LaGaO3 doped with Mg and Sr, gadolinium oxide doped cerium oxide, samarium oxide doped cerium oxide oxygen ion conductive electrolyte, or yttria stabilized zirconia electrolyte with the above electrolyte added to the surface as an isolation layer, or BaCeO3-based, SrCeO3-based, SrZrO3-based and BaZrO3-based ion conductive electrolyte.
6. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 1, characterized in that: The La x Sr 1-x Fe 0.9-y Ni y Mo 0.1 O 3-δ Powder or defect type (La x Sr 1-x ) 0.95 Fe 0.9-y Ni y Mo 0.1 O 3-δ The mass ratio of powder to organic binder and pore-forming agent is 5:5:
1.
7. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 1, characterized in that: A certain proportion of electrolyte powder is also mixed into the electrode slurry.
8. The in-situ construction method of a heterogeneous oxygen electrode for a solid oxide battery according to claim 1, characterized in that: In the first step, the transition metal element Ni doped at the B site is replaced by at least one of Co and Cu, or replaced by any of Ni, Co and Cu.
9. A solid oxide battery heterogeneous oxygen electrode prepared by the in-situ construction method according to any one of claims 1 to 8.
10. Use of the solid oxide cell heterogeneous oxygen electrode as claimed in claim 9 in the cathode of a solid oxide fuel cell, the anode of a solid oxide electrolysis cell or the oxygen electrode of a reversible solid oxide fuel cell.
